Crescimento da produtividade agrícola nas microrregi\~oes Brasileiras - Alexandre Xavier Ywata de Carvalho; Camilo Rey Laureto; Marina Garcia Pena (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– The Brazilian agricultural market is a key source of government revenues. Therefore, many studies are being done to assess the sector's productivity gain over time. This work focuses on mapping the gain of agricultural productivity in Brazil in the years 1990-2012 by micro-region. After an overview of the behavior of productivity in the major regions, will be studied the six major crops relative to the production value.The soybean, sugar cane, corn, coffee, cotton and cassava crops accounted, on average between 2010 and 2012, 72% of national production. These 23 years will be divided into two periods, justified by the existing economic outlook at the time: from 1990 to 2000 and 2001 to 2012. These two periods are compared in order to analyze the evolution of productivity over the years.
Keywords: Q10; N56; O13; 330; agricultural productivity; mapping; agriculture; micro-regions; Brazil